EKOLOGICAL DEVELOPMENT AND HUMAN PEDAGOGY (Scientific journal of the Fergana State University, 2024)
Taking into account the fact that the concept of ecology, reasonable attitude to nature, as well as environmental problems are gaining global importance in the system of pedagogical research all over the world, ecological concepts are being gradually explained and developed in the process of education of the young generation in all countries.